Aberrant Promoter Hypomethylation in CLL: Does It Matter for Disease Development? - Upchurch, Garland Michael; Haney, Staci L.; Opavsky, Rene (Frontiers in Oncology, 2016)
Over the last 30 years, studies of aberrant DNA methylation in hematologic malignancies have been dominated by the primary focus of understanding promoter hypermethylation. These efforts not only resulted in a better understanding of the basis of epigenetic silencing of tumor suppressor genes, but also resulted in approval of hypomethylating agents for the treatment of several malignancies such as myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). Recent advances in global methylation profiling coupled with the use of mouse models suggest that aberrant promoter hypomethylation is also a frequent event in hematologic malignancies, particularly in chronic lymphocytic leukemia (CLL). Promoter hypomethylation affects gene expression and therefore may play an important role in disease pathogenesis. Here we review recent findings and discuss the potential involvement of aberrant promoter hypomethylation in CLL.